Fenomena Literasi Informasi Hoax Pada Penyandang Disabilitas Tunarungu Smalb Santi Rama Jakarta - Koncara, Mochammad Nurfadill; Anggraini, Clara Novita (eProceedings of Management, 2023)
This study aims to reveal the phenomenon of hoax information literacy among people with hearing impairments at SMALB Santi Rama Jakarta. Through a qualitative approach with a case study method, data was collected through in-depth interviews with a number of people with hearing disabilities. The results show that their hoax information literacy is influenced by accessibility limitations, difficulties in understanding audiovisual information, and limitations in recognizing and sorting out valid information. In addition, social and environmental influences also play a role in influencing their perception of hoax information. These findings indicate the need to develop educational programs that focus on improving information literacy for people with hearing disabilities. Involving schools, families and communities, these programs aim to provide the necessary support for them to access, understand and sort out correct information. This research provides important insights into understanding the specific challenges and needs of information literacy in people with hearing impairments and encourages collaborative efforts to improve their information literacy.Keywords-information literacy, hoaxes, people with disabilities, hearing impaired, SMALB Santi Rama Jakarta